Sistem Pendukung Keputusan Penentuan Penerima Jaminan Kesehatan Masyarakat Dengan Metode SAW Pada RSUD Raden Mattaher Provinsi Jambi - Chairunnisa, Chairunnisa; Roestam , Rusdianto (LPPM Universitas Dinamika Bangsa, 2022)
RSUD Raden Mattaher Provinsi Jambi is a hospital owned by the Jambi Provincial Government located in the city of Jambi, established in 1948 with type C and joined with the Dinas Kesehatan Tentara (DKT). On November 19, 1972 it was moved to Jl. Lt. Gen. Suprapto No. 31 Telanaipura Jambi. This hospital was built on a land area of + 75,000 M2 with a building area of + 41,590 M2. Jaminan Kesehatan Provinsi (JAMKESPROV) is a health care effort whose financing is managed in an integrated manner. In addition, JAMKESPROV is a guarantee program for the payment of health care costs provided by the Jambi Provincial Government to the people of Jambi. The target of the Jamkesda Program is all people of Jambi Province who do not have health insurance in the form of Jamkesmas, ASKES and other health insurance. The Jambi Province Health Insurance program has weaknesses, among others, participant data is still not accurate, socialization is not optimal, and there are fees for getting cards. In addition, other problems are that there are participants who do not use the card when seeking treatment, the presence of Jamkesmas patients who incur costs, and the poor quality of service for Jamkesmas patients. To solve the problems that occur the authors conduct research and design a Decision Support System for Determining Acceptance of Public Health Insurance in the Health Sector with the SAW method. It is hoped that it can provide input and speed up the requirements process in supporting the decision of the recipient of the Public Health Insurance at RSUD Raden Mattaher Provinsi Jambi. And an alternative is to improve the Public Health Insurance service in determining who is entitled to Health Insurance at Raden Mattaher Hospital, Jambi Province. In this study, the UML (Unified Modeling Language) system modeling method includes Use Case Diagrams, Activity Diagrams and Class Diagrams.